A DESCRIPTIVE STUDY ON START-UP INDIA – PROGRESS TOWARDS DEVELOPMENT AND HARNESSING INNOVATION (International Journal of Food and Nutritional Sciences, 2022)
A startup is created company, partnership, or venture that aims to quickly expand an innovative business concept. A startup is a young, up-and-coming firm that takes a proactive towards creating a lucrative business model. An MVP (Minimum Viable Product) is a prototype used by startups to test and refine their fresh ideas and approaches to doing business. In addition, the company's founders engage in extensive studies and surveys to learn more about emerging ideas, technology, industry trends, and commercial opportunities. To affirm ownership, dedication and contributions of founders and investors, a shareholder's agreement needed to be agreed upon early on. The main aim of the research was to understand the start-ups and their significance and to measure the awareness level among young people about towards the Startup India – Progress towards Development and Harnessing Innovation highlights and to study the performance of startups as well as the role of various stakeholders. The research, which was undertaken in the month of October 2022. It is descriptive in character nature. Convenient sampling technique is used for the study with 150 participants as the sample size. People between the ages of 25 and 45 who express an interest in starting their own businesses are given preferential treatment. Google forms were used for the collection of the information from them.